Exploring the effects of service innovation ambidexterity on service design in the tourism and hospitality industry - Tajeddini, Kayhan; Gamage, Thilini Chathurika; Tajdini, Javad; Ul Hameed, Waseem; Tajeddini, Omid (Elsevier Sci Ltd, 2024)
Although the entrepreneurship strategy is demonstrated by evidence as a path to enhance the performance of service firms, the question of how it happens has yet to be adequately studied in the tourism and hospitality (T&H) realm. More specifically, how an entrepreneurial strategy enables a T&H firm to enhance its performance through service innovation exploration -exploitation ambidexterity has created a strategic dilemma in extant T&H literature. Constructed on the dynamic capabilities view and organizational ambidexterity theory, our paper addresses this dilemma using data from a drop -and -collect survey of 303 T&H firms in Japan. The findings reveal that entrepreneurial strategy fosters service innovation exploitation and service innovation exploration within T&H firms. In contrast, service innovation exploitation helps T&H firms design unique service offerings, yielding a sustained competitive advantage and superior corporate performance in the long run. Further, the availability of slack resources within T&H firms fosters service innovation exploration and service innovation exploitation.
Keywords: Entrepreneurial strategy; service innovation ambidexterity; service design; service innovation exploration; service innovation exploitation; sustained competitive advantage